Calorie Intake During Status Epilepticus and Outcome: A 5-Year Cohort Study. Issue 8 (August 2019) - Rybitschka, Anja; Semmlack, Saskia; Kaplan, Peter W.; De Marchis, Gian Marco; Rüegg, Stephan; Marsch, Stephan; Sutter, Raoul
Abstract : Objectives: Recommendations regarding nutrition during status epilepticus are lacking, and it is unclear whether restriction of calorie intake would result in beneficial effects or potential harm. We thus aimed to investigate associations between daily calorie intake and outcome in adult status epilepticus patients deriving from a 5-year cohort with a systematic and prospective collection of nutritional data. Design: Retrospective observational study. Setting: Medical ICUs at a tertiary academic medical care center. Patients: Consecutive patients with status epilepticus treated at the ICUs from 2012 to 2016 were included. Interventions: None. Measurements and Main Results: All patients with status epilepticus were monitored regarding nutrition support provided according to the guidelines. Relative risks of no return to baseline were estimated by Poisson regression with robust error variance and adjusted for potential confounders. Of 203 patients, 86 (42%) had return to baseline. Metabolic characteristics of patients with and without return to baseline did not differ. Patients without return to baseline received more calories and proteins per status epilepticus day, and increasing nutritional support was associated with ventilator-associated pneumonia (relative risk, 1.19; 95% CI, 1.09–1.28). Multivariable regression analysis revealed significant increases in relative risks for no return to baseline with every percent of days with nutrition (relative risk, 1.35; 95% CI, 1.05–1.74), with every 100 kcal (relative risk, 1.01; 95% CI, 1.002–1.01), and gram of protein intake (relative risk, 1.01; 95% CI, 1.001–1.01) per status epilepticus day, independent of potential confounders (including fatal etiology, duration and severity of status epilepticus, Charlson comorbidity index, and treatment with anesthetics). Conclusions: Our results indicate that increased calorie intake during status epilepticus is independently associated with unfavorable outcome. These findings require further validation and investigations into potential mediators, such as induction of ketogenesis, immunomodulating effects, and/or reduction of ICU-associated complications, such as infections.